IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL USING COMICS TO IMPROVE GEOGRAPHY LEARNING OUTCOMES OF GRADE IX IPS STUDENTS AT MAS UMMUL AYMAN SAMALANGA - Rifaizal, Muhammad; Ruliani, Ruliani; Kamil, Puspita Annaba (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2025)
Problem-based learning (PBL) is a learning model that can stimulate student activity. The combination of the PBL model with comic media is suitable for use in geography learning. So it can attract students' attention and make it easier to understand the learning material. The purpose of this study was to determine the improvement in learning outcomes, teacher and student activities, teacher skills in managing learning and student responses to learning. The approach used in this study was Classroom Action Research (CAR). The subjects in this study were 35 students of class XI IPS MAS Ummul Ayman Samalanga. Data sources in this study were students, teachers and collaborators. Data collection was carried out through tests, observations, documentation and student response questionnaires. The results showed that individual learning outcomes in cycle I increased from 29% to 40% in cycle II, and 86% in cycle III. Classically, the percentage of completeness in cycle I reached 50%, in cycle II reached 60% and increased to 80% in cycle III. Teacher and student activities in cycle I out of 10 activities in total are 8 appropriate activities, cycle II is 9 appropriate activities and in cycle III all activities are appropriate. Teacher understanding in cycle I obtained a score of 3.3 with a good category, in cycle II obtained a score of 3.4 with a good category and in cycle III obtained a score of 4 with a very good category. Student responses in general (86%) gave a positive response and very small (14%) students gave a negative response. Thus it can be concluded that the application of the Problem Based Learning model assisted by comic media can improve the geography learning outcomes of class XI IPS MAS Ummul Ayman Samalanga to be better.